Praktik Pembederaan Kembali (Reflagging) pada Kapal Penangkap Ikan - Ariadno, Melda Kamil (UI Scholars Hub, 2021)
The issue of fishing vessel has been a major concern in the coastal state such as Indonesia. In fact it has been considered a serious matter to be governed and regulated in international law regime. United Nations Convention on the Law of the Sea (UNCLOS) 1982 has enacted that there shall be conservation measures especially in regard to highly migratory fish stocks and straddling fish stock. Unfortunately, there is fraudelent practice of fishing vessel to do a “reflagging” as a means to obtain the right to fish by ignoring the conservation measures upon fisheries resources in the high seas. There are at least four major international measures that have been formed by states to address these problems either directly or indirectly, those are The Agreement to Promote Compliance with the International Conservation and Management Measures by Fishing Vessels on the High Seas (1993 FAO Compliance Agreement), The Agreement for the Implementation of the Provisions of the 1982 UNCLOS Relating to ther Conservation and Management of Straddling Stocks and Highly Migratory Fish Stocks 1995 (UNIA 1995), Code of Conduct for Responsible Fisheries (CCRF) and International Plan of Action to Prevent, Deter and Eliminate Illegal, Unreported and Unregulated Fishing (IPOA IUU).